The Importance of Soil Seed Bank Function in Studies of Grassland Degradation - Chao Chen; Wei He; John Scullion; Mike Wilkinson (Diversity)
The world’s grasslands are under increasing threat of degradation. Given the potential for multiple drivers of decline, precise diagnosis of degradation is best achieved by comparison with a local, sustainable grassland community. Comparisons of this kind are becoming increasingly common for regional grassland plant communities, but these studies largely overlook interactions between soil responses to system degradation and the effective functioning of the soil seed bank. Surveys of grassland degradation studies have revealed that only around 5% include information on soil seed bank composition and no one aspect of community structure features across all studies. Furthermore, the majority of studies provide information only on ground coverage, sward biomass or species diversity in the plant subcommunity, with very few including information on the health of the soil seed bank or how changes in the soil environment could drive further deterioration in the plant community size, structure or effective functioning of the soil seed bank. We consider that soil responses to sward degradation are likely to exacerbate rather than mitigate impacts on soil seed bank function, leading to a spiral of system degradation in the absence of timely and targeted intervention. We propose improvements for future studies seeking to diagnose and quantify grassland degradation.